2019
DOI: 10.1190/geo2018-0298.1
|View full text |Cite
|
Sign up to set email alerts
|

What controls the initial peak of an air-gun source signature?

Abstract: Seismic air guns are broadband sources that generate acoustic waves at many frequencies. The low frequency waves can be used for imaging while the high frequency waves are attenuated and/or scattered before they can reflect from targets of interest in the subsurface. It is desirable to reduce the amplitude of the high frequency acoustic waves as they are thought to be disruptive, and potentially damaging, to marine life and are not useful for geophysical purposes. The high frequency acoustic waves are primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…To reduce the environmental impact, the high-frequency content should be controlled below a safety level. Many studies have shown that the rise time of the first pressure peak is an indicator of highfrequency content generated [7,8,16]. As can be seen in the inset of Figure 13 (a), a decreasing R c also decreases the slope of the first peak and the high-frequency content.…”
Section: The Impact Of the Cylinder On Realistic Airgun-bubblesmentioning
confidence: 83%
See 2 more Smart Citations
“…To reduce the environmental impact, the high-frequency content should be controlled below a safety level. Many studies have shown that the rise time of the first pressure peak is an indicator of highfrequency content generated [7,8,16]. As can be seen in the inset of Figure 13 (a), a decreasing R c also decreases the slope of the first peak and the high-frequency content.…”
Section: The Impact Of the Cylinder On Realistic Airgun-bubblesmentioning
confidence: 83%
“…As can be seen in the inset of Figure 13 (a), a decreasing R c also decreases the slope of the first peak and the high-frequency content. Recently, Watson et al [7] found that the air release rate and consequently the first pressure wave depend on the airgun length. Specifically, due to the influence of the rarefaction wave inside the chamber, a longer airgun causes a slower decay of the first pressure wave and hence reduced high-frequency content.…”
Section: The Impact Of the Cylinder On Realistic Airgun-bubblesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this gather, scattered energy due to the presence of the salt body is clearly visible within the observed events. Moreover, it is clearly evident that the data processing removed the reverberation due to the air-gun-bubble oscillations (Watson et al, 2019). The processed data are used in all steps of this application: velocity model building, RTM, and extended linearized waveform inversion.…”
Section: Field-data Examplementioning
confidence: 99%
“…In addition, such knowledge will help us to design more environmentally friendly air-gun sources and optimize the signal toward the seismic band of interest. In that respect, Watson et al (2019) focus on the initial peak in their investigation on how physics and source parameters influence the signature of an air gun. Christie et al (2019) clearly demonstrate that a secondary "cavity source" can be assigned as an extra notional source.…”
Section: Introductionmentioning
confidence: 99%